Redes sociais e campanha política: convergência midiática na eleição de 2012 para prefeito de João Pessoa - Santos, Joceane Gomes dos (2015)
The press, radio and television have historically occupied strategic places with regard to electoral propaganda, especially on the use of their language by the candidates. With the advent of internet and social networks, there are changes in techniques, languages and media narratives as well as new arrangements of participation and sociability, in particular the television context, because of the strength this vehicle has with the electorate. Among the changes in digital communication, we point out the processes "transmedia" (JENKINS, 2009), "interaction" (PRIMO, 2007) and "media convergence" (CASTRO & DUARTE, 2010), in which the languages of different media merge. This work includes the narratives used in the campaigns of candidates for mayor of the city of João Pessoa-PB and observes the processes of "transmediation" "interactivity" and "media convergence". This work also seeks to examine how social networks is becoming a propitious locus for the announcement of election messages, and the use of "transmedia storytelling" in the political environment. The media convergence imposes a new modus operandi in the work routine of professionals working in the political field, demanding that they recognize the power of network communication and adapt their language to the contingencies of this "new communication" (CHAREAUDAU, 2008). The communication shared through the network generates modes of interaction and sociability, encouraging citizens-voters to defend their interests, to make their choices and to take their own decisions, without prioritizing profitable ambitions of corporate communication (ANTOUN & MALINI, 2013). From this perspective, we proposed an analysis of the social networks Twitter and Facebook, considering the effectiveness of theiruse in the elections of 2012.